Prevalence of Chronic Rhinosinusitis in the Setting of Behçet Disease. Issue 1 (January 2015) - Verim, Ayşegül; Cebeci, Filiz; Başer, Engin; Çalim, Ömer Faruk; Kadioğlu, Dinçer; Kocagöz, Gamze Didem
<x xml:space="preserve">Abstract</x> Abstract Behçet disease (BD) is a systemic autoimmune/autoinflammatory, T helper 1–mediated condition. It is well known that the prevalence of a T helper 1–mediated disease increases in the presence of another T helper 1–mediated comorbidity. The purpose of this study was to investigate the prevalence of T helper 1–mediated chronic rhinosinusitis without nasal polyposis (CRSsNP) and T helper 2–mediated chronic rhinosinusitis with polyposis in the presence of comorbid BD. Sixty-nine patients and 74 healthy controls were included in the study. Participants were asked to complete a questionnaire for symptoms of rhinosinusitis. Nasal cavities were scored using the Lund-Kennedy endoscopy scores. Paranasal sinus computed tomography imagings were scored according to Lund-Mackay radiology scores. Skin prick tests were carried out for all participants to determine the predisposing role of allergy (T helper 2 disease) in the etiopathogenesis of rhinosinusitis among patients and controls. Patients' endoscopy, radiology, and skin prick testing scores were evaluated with regard to BD activity. The prevalence of CRSsNP was 23.2 % in BD and 2.7% in normal population. The CRSsNP was more frequently seen in patients than in the healthy controls (P = 0.002). The BD patients displayed worse scores on their left sinonasal endoscopy. No statistically significant difference was seen between BD and control groups with regard to Lund-Mackay radiology scores of both sides. The presence of an allergic response to a specific allergen in skin-prick testing were confirmed in 25 patients (36.2%) and 17 controls (23.0%). However, the difference was not statistically significant. There were positive responses to more allergens when BD activity was reduced. The CRSsNP thought to be of T helper 1–mediated origin was more frequently seen in the presence of comorbid BD.